Welfare office. - United States. Army. Signal Corps (photographer):::Creator::::::::::::; Flaherty, John Melvin (collector):::Contributor::::::::::::
Photograph shows an evacuee consulting a staff adviser at the Fresno, California Assembly Center Welfare Office.